Prediction of fatigue life on lower suspension arm subjected to variable amplitude loading - Zulkifli, Husin (2010)
This project focuses on the finite element based fatigue life prediction of lower suspension arm subjected to variable amplitude loading using different fatigue methods. Objectives of this project are to predict fatigue life of the lower suspension arm using stress-life and strain-life methods, to investigate the effect of the mean stress and to identify the suitable material for the suspension arm. The lower suspension arm was developed using computer aided design software. The finite element modeling and analysis were performed utilizing the finite element analysis code. The finite element analysis was performed using MSC.NASTRAN code using the linear elastic approach. In addition, the fatigue life analysis was performed using the stress-life and strain-life approach subjected to variable amplitude loading. The three types of variable amplitude are considered including positive mean loading (SAETRN), compressive mean loading (SAESUS) and zero mean loading (SAEBKT). It can be seen that TET10 mesh and maximum principal stress were captured the maximum stress. From the fatigue analysis, Goodman method is predict the conservative result when subjected to SAETRN and SAESUS loading while SWT method is applicable in SAEBKT loading. Stress-life is capable to give higher fatigue life when subjected to SAEBKT while strain-life method is applicable to give higher fatigue life when subjected to SAETRN and SAESUS. From the material optimization, 7175-T73 aluminum alloy is suitable material of the lower suspension arm.